GAMBARAN PENGETAHUAN DAN SIKAP PERAWAT TERHADAP TINDAKAN KOMPRES HANGAT PADA PASIEN HIPERTERMI - Syahfitri, Ria Dila; Budi, Setia (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Hypertermi is a condition when an individual experiences or risks experiencing a continuous increase in body temperature of more than 37.8 ° C (100 ° F) orally or 38.9 ° C (101 ° F) per rectal due to external factors. Hypertermi is the onset of symptoms in a disease, which begins with an increase in body temperature in the patient, and the usual initial action is to do a warm compress because warm compresses can lower the body temperature of patients with hyperthermia. Knowledge is the result of knowing that happens after someone observes a particular object, while attitude is a feeling of support or partiality or a feeling of not supporting or not favoring the object. Nurses who provide nursing care should have knowledge, and a good attitude in lowering body temperature. The impact of a lack of knowledge, and the attitude of nurses will result in an optimal decrease in heat in patients. The purpose of this study was to determine the description of nurses' knowledge and attitudes towards the action of warm compresses in hypetermic patients in the Aster Childhood Disease Room at TK.II Hospital Dr.AK. Gani Palembang. The design of this study is quantitative descriptively, while the number of samples is 19 people. Samples taken using nonprobability sampling technique with accidental sampling method, the data used is primary data using a questionnaire, the respondents studied were nurses in the Aster Room, the time of the study during August 2017. The results obtained that the level of good knowledge is 73 , 7% (14 people), and nurses who have positive attitudes as many as 16 people (84.2%). The advice that can be given is to further improve the knowledge and attitudes of nurses about the action of warm compresses. Keyword : Knowledge, Attitude, Hypertermi, Warm Compress